College Students’ Academic Achievement: Exploring the Role of Hope and Academic Self-Efficacy - Penzar, Esther C.; Shea, Munyi; Edwards, Cher N. (International Dialogues on Education Journal, 2021)
In the present study, the relationships among trait hope, academic self-efficacy, and academic achievement (self-reported GPA) were examined among college students. Demographic differences were analyzed based on college-going status, ethnicity, and gender. First-generation college-going students (FGCS) reported significantly lower levels of hope, academic self-efficacy, and academic achievement when compared to non-FGCS. Male students reported significantly lower academic self-efficacy compared to female students. There was no statistically significant difference between non-White and White students. Overall, academic self-efficacy was a stronger predictor of achievement than hope. Between the two subscales of trait hope, agency was more strongly correlated with academic achievement than pathways. Furthermore, a mediation analysis indicated that academic self-efficacy fully accounted for the relationship between agency and academic achievement, which suggests that perceived capacity and agency to perform tasks in a specific domain may be more strongly associated with academic achievement than a general sense of hope and motivation.